Dysfunctional Attitudes in Alcohol Dependents: A Comparative Study - Görkem Karakas Ugurlu; Mustafa Uğurlu; Levent Turhan; M. Hakan Türkçapar (Bilişsel Davranışçı Psikoterapi ve Araştırmalar Dergisi)
Objective: Cognitive behavioral theory provides a theoretical framework for understanding the etiology and persistence of pathological drinking, and a conceptual basis for developing clinical techniques to treat the disorder. In line with this scope, we aimed to investigate the cognitive properties of alcohol dependence. Method: Two groups composed of seventy-nine inpatients with a diagnosis of alcohol dependence and thirty one healthy controls who were using alcohol, but not filling the requirements of alcohol dependence diagnosis were included in this study. Dysfunctional attitudes scale (DAS) was given to both groups for detection of dysfunctional cognition. At the same time, alcohol dependent group was evaluated using Structured Clinical Interview for DSM-III-R-Axis-I and Axis-II (SCID I and II). The data was evaluated using SPSS 17. Results: DAS total scores and perfectionist attitudes, need for approval and independent attitudes subscores were significantly higher in patients than healthy controls. In addition, a significant correlation was detected between DAS total scores, and the age of emergence of alcohol dependence. Conclusion: As a result of the study, it can be concluded that concluded with literature, alcohol dependent patients have dysfunctional beliefs. In particular, a relation was detected between alcohol dependence and perfectionist attitude, need for approval and independent attitudes.